Epidemiologic distinctions between base of tongue and tonsil oropharyngeal carcinomas. Issue 10 (20th July 2021) - Windon, Melina J.; Fakhry, Carole; Margalit, Danielle N.; Dey, Tanujit; Rettig, Eleni M.
Abstract: Background: Human papillomavirus (HPV)‐positive tonsil and base of tongue (BOT) cancers have been considered together. However, important differences may exist. Methods: Demographic and tumor characteristics, and survival, were compared by oropharyngeal cancer subsite from 2004 to 2016 in the National Cancer Database (NCDB). Trends in tonsillectomy from the National Health and Nutrition Examination Survey (NHANES) 2011–2014 were examined. Results: HPV‐positive BOT ( N = 13 081) were older than HPV‐positive tonsil patients ( N = 16 874; mean 61.5 vs. 58.4 years, p < 0.001), and individuals 70+ years were significantly more likely to have BOT tumors compared with individuals <50 (adjusted odd ratio [aOR] = 2.9, 95% confidence interval = 2.6–3.2). BOT patients were also more likely to be white, male, and have advanced tumor classification. Among 7418 NHANES participants, tonsillectomy was associated with older age and white race. Conclusions: There are epidemiologic and tumor‐related differences among HPV‐positive tonsil and BOT carcinomas. Demographic differences may be attributable to tonsillectomy trends.